Seeking empowerment to comfort patients in severe pain: A grounded theory study of the nurse's perspective - Slatyer, Susan; Williams, A.; Michael, R. (Elsevier Ltd, 2015)
© 2014 Elsevier Ltd.Background: Hospital patients experience significant pain, which can delay healing and increase the risk of developing chronic pain. Nurses are affected by patients' ongoing pain and may cope with consequent anxiety and helplessness by distancing themselves from such patients. Understanding nurses' responses to patients in severe pain will inform strategies to support their coping, their patients and, ultimately, their retention in the nursing workforce. Objectives: The aim of the study was to develop a substantive theory explaining the hospital nurse's perspective of caring for patients in severe pain. Design: The study used grounded theory method. Settings: Data were collected on four acute care wards in a 610 bed Australian hospital. Participants: The sample included 33 nurse participants and 11 patient participants. Selection criteria for nurse participants were those who worked in the four study wards, cared for patients who experienced severe pain, and consented to be included. Selection criteria for patient participants were those who self-reported pain at intensity of seven or more on a scale of 0-10, were aged 18 years or older, could speak and read English, and consented to be included. Methods: Theoretical sampling directed the collection of data using semi-structured interviews with nurses and participant observation, including structured observations of nurses who cared for patients in pain. Data were analysed using constant comparison method. Results: Nurse participants encountered a basic psychosocial problem of feelings of disempowerment when their patients experienced persisting severe pain. In response, they used a basic psychosocial process of seeking empowerment to provide comfort in order to resolve distress and exhaustion associated with disempowerment. This coping process comprised three stages: building connections; finding alternative ways to comfort; and quelling emotional turmoil. Conclusions: The substantive theory proposed a link between the stress of nurses' disempowerment and a coping response that provides direction to support nurses' practice. Strategies indicated include enhanced communication protocols, access to advanced practice nurses, use of nonpharmacological comfort measures, utilization of ward-based pain resource nurses, and unit-specific pain management education. Further research to verify and extend the substantive theory to other settings and nursing populations is warranted.